PENGELOLAAN INFRASTRUKTUR BERDASARKAN ISU BERKELANJUTAN DI INDONESIA - Ervianto, Wulfram Indri (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
ABSTRACT Environmental degradation characterized by the occurrence of global warming phenomenon is a concern to many parties. The construction sector as one of the parties using natural resources in the form of manufacturing or natural material needs to evaluate the activity of the construction process. Indonesia as a developing country requires various types of infrastructure, one of which is building construction. Various studies show that the impact of the construction process produces a large number of wastes and causes a decrease in the number of non-renewable materials. One of approaches to organize those impacts is by applying the principle of green construction. The purpose of this research is to develop green construction assessment model for building construction in Indonesia to improve the performance of contractor in the construction process. Key words : Environment Degradation, Construction Process, Environment Friendly ABSTRAK Terjadinya degradasi lingkungan semakin besar di berbagai negara di dunia dan menjadi perhatisn banyak pihak. Salah satu sektor yang menggunakan sumberdaya alam relatif besar adalah sektor konstruksi. Indonesia sebagai negara berkembang sedang membangun berbagai jenis infrastruktur diantaranya adalah bangunan gedung. Berbagai penelitian menyatakan bahwa dampak proses pembangunan adalah ditimbulkannya limbah dalam jumlah besar termasuk sumberdaya alam yang bersifat tak terbarukan. Oleh sebab itu diperlukan pendekatan yang mampu mengakomodasi hal tersebut yaitu green construction. Tujuan penulisan ini adalah memformulasikan pendekatan ramah lingkungan untuk infrastruktur, salah satunya bangunan gedung. Kata Kunci: Degradasi lingkungan, Proses konstruksi, Ramah lingkungan.